Assessment of apical pressures at different automated irrigant flow rates: an ex vivo study based on computational fluid dynamic analysis - Choudhari, Sahil; Teja, Kavalipurapu Venkata; Ramesh, Sindhu; Jose, Jerry; Janani, Krishnamachari; Kumar, Raja (Brazilian Dental Science, 2022)
Objective: The current study aimed at assessing the induced apical pressure at various simulated irrigantflow rates. Materials and Methods: Forty eight freshly extracted single-rooted premolars were decoronatedand prepared to size 30 0.04 taper using HY-Flex CM rotary file system and were scanned using cone-beamcomputed tomography (CBCT). The scanned images were reconstructed to three-dimensional Computer-aideddesign models (CAD) and the 3D needle was also reconstructed. Finally, simulations were done by placing the30 gauge open-ended needle 3 mm short of the working length. Results: There was a statistically significantdifference (p